Pemanfaatan Media Sosial Tik Tok Dalam Optimalisasi Branding Produk Frozen Food di UMKM MaprahMas Desa Silir Kecamatan Wates Kabupaten Kediri - Sholikah, Vedila; Suryawati, Ika; Cahyani, Putri Ekamalia; Aini, Intan Nur; Mukaromah, Siti Zakiyatul; Cahya Yulian Tri Nanda; Amaliyah, Farah; Afandi, Akhmad Jazuli; Qutsam, Zayyan Huwaida Azarine Sifa (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2025)
The rise of digital technology has changed the way micro, small, and medium enterprises (MSMEs) market their goods. TikTok is one of the most popular social media platforms today and has great potential to be used in the marketing industry. The purpose of this study is to investigate how the use of social media on TikTok can be optimized for product branding in micro, small, and medium enterprises (MSMEs). The method used is a case study using mixed methods (mixed methods with qualitative and quantitative approaches), and the results show that the use of TikTok can increase product visibility and build strong relationships with brands. However, this study shows that TikTok is a potential social media resource that micro, small, and medium-sized enterprises (MSMEs) can optimize to improve their product brand image while increasing competitiveness in the digital era. In addition, the success of branding on TikTok is also influenced by content consistency, understanding the target audience, and the right digital marketing strategy.